PERSEPSI MASYARAKAT KAMPUNG KUSAMBA TERHADAP MAKNA POLITIK MULTIKULTURALISME - Dewi, I.A Gede Indrialistika; Bandiyah, Bandiyah; Azhar, Muhammad Ali (Jurnal Nawala Politika; 2016, 2016)
ABSTRACK Multiculturalism that occurred in the village kusamba to explain how the public perception of the village kusamba to the meaning of the politics of multiculturalism in klungkung, revealed how the patterns of relationship Muslim-Hindu of Bali. Perception in the village Kusamba be classified into three parts, namely, the public perception among the elite, the public perception among the middle and the public perception of society, common perception has the classified into three parts to know how the difference, justice and equality of each of the public perception in home village kusamba and village kusamba to the meaning of the politics of multiculturalism that happened. As a step a theoretical, this study uses the theory of multiculturalism which was said to be an amplifier to create the harmony among religious in the village of Kusamba who have the diversity of culture and religion. the religious harmony the village kusamba not only on tolerance, but.equality of all elements of society that materialized in the whole social, cultural, even in the political space. The method used in this study is the method of qualitative descriptive, while the techniques of collecting data through interviews, study documentation and analysis of documents. In the analysis of the findings in the field showed that there are differences and similarities to the public perception in the village kusamba and the values of multiculturalism that is embedded in generations and how a society able to cling to tolerance has been undertaken for a long time until today. Keywords: Public Perception, Kampung Kusamba, Politics of Multiculturalism